Effect of Black Cumin Cake Extract, Octyl Caffeate, and Active Packaging on Antioxidant Properties of Egg-Free Mayonnaise during Storage - Katarzyna Włodarczyk; Alicja Tymczewska; Dobrochna Rabiej-Kozioł; Aleksandra Szydłowska-Czerniak (Applied Sciences, 2023)
The egg-less mayonnaise (CM) based on aquafaba and refined rapeseed oil was prepared and enriched with black cumin cake extract (BCCE) at two concentrations of 0.1% (BCCM0.1%) and 3% (BCCM3%) and 0.1% of octyl caffeate (OCM). The obtained mayonnaises were placed in glass jars without and with active film incorporating BCCE at the jar bottom (AFM). The influence of antioxidants on oxidative stability and antioxidant capacity (AC) of the prepared mayonnaises was estimated by the shelf-life test. Peroxide value (PV), anisidine value (AnV), total oxidation (TOTOX) value, acid value (AV), and amounts of conjugated dienes (CD) and conjugated trienes (CT) were used to assess the extent of mayonnaise deterioration during storage of up to 4 weeks in a refrigerator. The synthesized octyl caffeate (OC) and natural antioxidants from BCCE added to mayonnaises directly and released from active film enhanced the AC of the studied mayonnaise samples determined using the QUick, Easy, New, CHEap, and Reproducible-2,2-diphenyl-1-picrylhydrazyl (QUENCHER-DPPH), and QUENCHER-2,2′-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (QUENCHER-ABTS) methods. All enriched mayonnaises had higher antioxidant potential than the AC of the control sample without antioxidants (CM) and commercial plant-based mayonnaise (CPBM). Therefore, the proposed antioxidants and active film can be used in the food industry to suppress lipid oxidation.